ОСОБЕННОСТИ ФУНКЦИОНИРОВАНИЯ УРБАНИЗИРОВАННОГО ВОДОСБОРНОГО БАССЕЙНА (НА ПРИМЕРЕ БАССЕЙНА Р. ХОДЫНКИ, Г. МОСКВА) - Федорович Д.В.; Маккавеев А.Н.; Локшин Г.П.; Горецкий К.В. (My University, 2004)
Seven types of relatively homogeneous natural-technogenic subsystems were revealed within the basin of Hodynka - the left tributary of the Moscow river. Geomorphologic and hydrologic conditions, man-made changes of relief, vibrating effects play a great role in stability or instability of the subsystems. Ground water level changes in the ancient valley governed the activation of karst and suffusion.
Keywords: 551.438.5(470.311)